DIREITOS HUMANOS E O SISTEMA DE JUSTIÇA CRIMINAL SOB ÓTICA DOSPOVOS INDÍGENAS NO MATO GROSSO DO SUL - PRISCILA CAETANO AMORIM (2025)
This research examines the problems of criminal justice in the state of Mato Grosso do Sul, focusing on the intersection between the traditional legal system and the rights of indigenous peoples. The analysis focuses on the complex relationship between the policy of formation of the criminal justice system, legal pluralism, and the reality faced by indigenous peoples in the context of incarceration. It seeks to explore the following problematic: How does the criminal justice system, shaped by a policy of integrationist, Eurocentric, and colonial bias, impact the rights of indigenous peoples in Mato Grosso do Sul, and how can legal pluralism contribute to the construction of a more balanced system? In addition to being a deductive research, the method proposed for this research on the challenges faced by indigenous peoples in the Brazilian prison system is based on a comprehensive approach that combines quantitative and qualitative techniques (data from official reports and bibliographic research). This methodology was carefully designed to provide a deep and holistic understanding of the issues under analysis, as well as to identify opportunities for intervention and policy formulation.